Use \( \lim _{x \rightarrow c} f(x)=-2 \) and \( \lim _{x \rightarrow c} g(x)=-7 \) to find the limit. \[ \lim _{x \rightarrow c}[6 f(x)-4 g(x)] \]
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To find the limit \( \lim _{x \rightarrow c}[6 f(x)-4 g(x)] \), you can use the properties of limits. First, apply the limits to \( f(x) \) and \( g(x) \): \[ \lim _{x \rightarrow c}[6 f(x)] = 6 \lim _{x \rightarrow c}[f(x)] = 6(-2) = -12, \] \[ \lim _{x \rightarrow c}[-4 g(x)] = -4 \lim _{x \rightarrow c}[g(x)] = -4(-7) = 28. \] Now combine these results: \[ \lim _{x \rightarrow c}[6 f(x)-4 g(x)] = -12 + 28 = 16. \] Thus, the limit is \[ \lim _{x \rightarrow c}[6 f(x)-4 g(x)] = 16. \]